A review of picobiine mites (Acari: Syringophilidae: Picobiinae) parasitising African birds - Skoracki, Maciej; Hromada, Martin (Folia parasitologica, 2013)
A fauna of quill mites of the subfamily Picobiinae (Acari: Syringophilidae) associated with African birds is revised. Two new monotypic genera are proposed, Gunabopicobia gen. n. for Picobia zumpti Lawrence, 1959 and Lawrencipicobia gen. n. for Picobia poicephali Skoracki et Dabert, 2002. These new genera differ from other genera of the subfamily by the following features: in females of Gunabopicobia, propodonotal setae vi are situated anterior to the level of setae ve; the narrow lateral propodonotal shields bear bases of setae vi, ve, si and se; the bases of setae 1a-1a are coalesced; the genital setae and the opisthosomal lobes are absent; the leg I with full set of solenidia and apodemes I are devoid of the thorn-like protuberances in the middle part. In females of Lawrencipicobia, the bases of setae 1a-1a are not coalesced; the propodonotal shield is entire; the genital setae are present; legs I are with full set of solenidia. Additionally, two new species belonging to Picobia Haller, 1878 are described, Picobia illadopsae sp. n. parasitising Illadopsis rufipennis (Sharpe) (Passeriformes: Pellorneidae) in Kenya and Picobia phoenicuri sp. n. infecting Phoenicurus moussieri (Olphe-Galliard) in Tunisia. The following species are redescribed, Columbiphilus alectoris (Fain, Bochkov et Mironov, 2000), Lawrencipicobia poicephali (Skoracki et Dabert, 2001) comb. n. and Picobia phoeniculi (Fain, Bochkov et Mironov, 2000). The key to the genera of the Picobiinae is provided.
Keywords: Bird Diseases; nemoci ptáků; infestace roztoči; Afrika; ptáci; Birds; Animals; Mites; Africa; zvířata; roztoči; Mite Infestations